Enhancing Learning Motivation in Islamic Religious Education: The Role of Sahabat Anak Muslim Comics among Elementary School Students - Muhammad Husnur Rofiq; Ahmad Ali Shah; Ashimatul Alai; Istiqomah Istiqomah (Institut Agama Islam Daruttaqwa Gresik, 2025)
The background of the study is based on the low interest and motivation of students in participating in Islamic Education learning, which still dominantly uses conventional lecture methods. This study aims to measure the effect of Comic media Sahabat Anak Muslim on increasing student learning motivation in Islamic Religious Education (PAI) subjects at the elementary school level. This study used a quantitative approach with an experimental Pretest-Posttest Control Group design. The research subjects comprised 72 students in grades V and VI at SDN Gondang, which were divided into experimental and control groups. The instrument in the form of a learning motivation test was given before and after treatment. The results showed an increase in the average score from 77.22 to 77.78 in the experimental class, while the control class increased from 71.81 to 72.50. The paired sample t-test showed that the increase was statistically significant (p < 0.05). This finding contributes to the innovation of visual and narrative-based learning media in Islamic character education. Comic press is proven to increase students’ engagement and understanding of teaching materials in a contextual and fun way. This study suggests the need for further exploration with more diverse samples and levels of education to gain a more comprehensive and in-depth understanding of the effectiveness of educational media in religious education.